Drug-Related Problems Pada Penyakit Paru Obstruksi Kronis: Literatur Review - Fahmi, Muhammad Zaini; Karuniawati, Hidayah; Ismail, Wan Ismahanisa (Journal of Pharmaceutical and Sciences, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of global morbidity and mortality, with a continuously increasing health burden. The complexity of long-term therapy in COPD increases the risk of Drug-Related Problems (DRPs), which can affect patient clinical outcomes. This literature review was conducted descriptively by searching articles in the PubMed, Scopus, Google Scholar, and ScienceDirect databases using keywords related to DRPs and COPD. The selection was made on publications from the last 10 years (2015–2025) relevant to the topic and available in full text. Based on studies by Li et al., (2019) and Apikoglu-Rabus et al., (2016), the classification of DRPs according to PCNE V9.0 mainly included aspects of medication safety (54.2%), inappropriate drug selection (up to 8.7%), excessive dosage (19.9%), excessive duration of therapy (17.7%), and errors in the drug use process (up to 63.3%). Patient factors such as non-compliance (25%) and incorrect inhalation techniques were the main contributors to the occurrence of DRPs. Inappropriate use of medications, drug-herb interactions, and lack of therapy monitoring were also consistently found. The findings suggest that DRPs significantly worsen symptom control and increase the risk of exacerbations. Pharmacists are critical in identifying, preventing, and managing DRPs through patient education, therapy review, and ongoing therapy monitoring. DRPs in COPD patients are a serious challenge that requires a multidisciplinary approach. Ongoing education, monitoring of therapy rationality, and collaboration between healthcare professionals are needed to improve patient safety and the effectiveness of COPD treatment.